2011
DOI: 10.1007/s00421-011-2080-3
|View full text |Cite
|
Sign up to set email alerts
|

The organization of upper limb physiological tremor

Abstract: The objectives of this study are (1) to assess the relationship between tremor displacement of different segments of the upper limb, (2) to assess whether an attempt to voluntarily reduce tremor amplitude affects this relationship. Twenty-five young healthy participants were tested. Tremor of the finger, hand, arm and shoulder was assessed using laser displacement sensors while the upper limb was in a postural position. Results show strong correlations (r > 0.90), high coherence (>0.9) and in-phase movement be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Tremor is usually altered by changes in spindle reflex loop times and the viscoelastic properties of tendons and ligaments. 34,35 Tendons form a series of elastic components in muscle, 36 and changes in laxity can alter both the amplitude and frequency of tremor. 35 The data for men were the same as those for women during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Tremor is usually altered by changes in spindle reflex loop times and the viscoelastic properties of tendons and ligaments. 34,35 Tendons form a series of elastic components in muscle, 36 and changes in laxity can alter both the amplitude and frequency of tremor. 35 The data for men were the same as those for women during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented that the PT in the upper extremity is largely driven by the limb mechanics enhanced by stretch reflex oscillation, but with minimal central influences (Elble, 2003;Raethjen et al, 2004;Raethjen, Pawlas, Lindemann, Wenzelburger, & Deuschl, 2000). In line with this, Carignan, Daneault, and Duval (2012) have found that tremors of all segments are highly correlated and driven by the angular displacement in the shoulder joint.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have documented, that the PT in the upper extremity is mostly driven by limb mechanics with minimal central influence [38][39][40]. In line with this finding, Carignan et co-workers discovered that tremors of all segments are driven by the angular displacement in the shoulder joint [41]. Side differences in the tremor intensity are not age, gender or laterality dependent, but are dictated by the segment's weight and dimensions [39].…”
Section: Discussionmentioning
confidence: 82%